Naturalization Proclivities, Ethnicity and Integration - Amelie Constant; Liliya Gataullina; Klaus F. Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
This paper studies the determinants of naturalization among Turkish and ex-Yugoslav immigrants in Germany differentiating between actual and planned citizenship. Using the German Socio-Economic Panel, we measure the impact that integration and ethnicity indicators exert on the probability to naturalize beyond the standard individual and human capital characteristics. A robust finding is that German citizenship is very valuable to female immigrants and the generally better educated, but not to those educated in Germany. We find that the degree of integration in German society has a differential effect on citizenship acquisition. While a longer residence in Germany has a negative influence on actual or future naturalization, arriving at a younger age and having close German friends are strong indicators of a positive proclivity to citizenship acquisition. Likewise, ethnic origins and religion also influence these decisions. Muslim immigrants in Germany are more willing to become German citizens than non-Muslim immigrants, but there are also fewer German citizens among Muslims than among non-Muslims.
Keywords: F22; J15; J61; 330; Citizenship; naturalization; ethnicity; integration